Carfilzomib, bendamustine, and dexamethasone in patients with advanced multiple myeloma: The EMN09 phase 1/2 study of the European Myeloma Network. Issue 18 (28th June 2021) - Gay, Francesca; Günther, Andreas; Offidani, Massimo; Engelhardt, Monika; Salvini, Marco; Montefusco, Vittorio; Patriarca, Francesca; Aquino, Sara; Pönisch, Wolfram; Spada, Stefano; Schub, Natalie; Gentili, Silvia; et al.
Abstract : Background: Combined therapy with carfilzomib, bendamustine, and dexamethasone was evaluated in this multicenter phase 1/2 trial conducted within the European Myeloma Network (EMN09 trial). Methods: Sixty‐three patients with relapsed/refractory multiple myeloma who had received ≥2 lines of prior therapy were included. The phase 1 portion of the study determined the maximum tolerated dose of carfilzomib with bendamustine set at 70 mg/m 2 on days 1 and 8. After 8 cycles, responding patients received maintenance therapy with carfilzomib and dexamethasone until progression. Results: On the basis of the phase 1 results, the recommended phase 2 dose for carfilzomib was 27 mg/m 2 twice weekly in weeks 1, 2, and 3. Fifty‐two percent of patients achieved a partial response or better, and 32% reached a very good partial response or better. The clinical benefit rate was 93%. After a median follow‐up of 21.9 months, the median progression‐free survival was 11.6 months, and the median overall survival was 30.4 months. The reported grade ≥3 hematologic adverse events (AEs) were lymphopenia (29%), neutropenia (25%), and thrombocytopenia (22%). The main nonhematologic grade ≥3 AEs were pneumonia, thromboembolic events (10%), cardiac AEs (8%), and hypertension (2%). Conclusions: In heavily pretreated patients who have relapsed/refractory multiple myeloma, combined carfilzomib, bendamustine, and dexamethasone is an effective treatment option administered in the outpatient setting. Infection prophylaxis and attention to patients with cardiovascular predisposition are required. Abstract : In patients with heavily pretreated relapsed/refractory multiple myeloma, combined carfilzomib, bendamustine, and dexamethasone is an effective, well tolerated, and affordable treatment option safely administered in the outpatient setting. However, infection prophylaxis and attention to patients with cardiovascular predisposition are required.